2016
DOI: 10.3998/ark.5550190.p009.347
|View full text |Cite
|
Sign up to set email alerts
|

Phenazines as chemosensors of solution analytes and as sensitizers in organic photovoltaics

Abstract: This review aims to highlight phenazines as photoactive molecules with applications arising from its unique optical properties. Synthesis and optical spectra of a number of phenazines possessing absorption and emission signals in the visible range was reported. Applications described included sensing of cations, anions and as sensitizers in organic photovoltaics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The origin of the absorption peaks is due to p-p* transitions and possibly a small charge transfer component from substituents to the quinoxaline unit. 36 It was found that the larger the conjugated p bond system, the more red-shifted the absorption maximum.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the absorption peaks is due to p-p* transitions and possibly a small charge transfer component from substituents to the quinoxaline unit. 36 It was found that the larger the conjugated p bond system, the more red-shifted the absorption maximum.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the nature of the phenazine redox ability to transfer the charge from the pyrazine core to benzylamine, the process was followed by UV–vis spectroscopy, similarly as presented above (Figure ). 1a shows a strong absorption peak in the range 250 to 400 nm, primarily due to π–π* transitions of the phenyl rings around the pyrazine core . After the addition of NOBF 4 as the oxidizing agent, the main adsorption band broadens to the range 250 to 480 nm, while a new band appears in the range 500 to 750 nm (strong change of color from colorless to green).…”
Section: Resultsmentioning
confidence: 99%
“…1a shows a strong absorption peak in the range 250 to 400 nm, primarily due to π−π* transitions of the phenyl rings around the pyrazine core. 38 After the addition of NOBF 4 as the oxidizing agent, the main adsorption band broadens to the range 250 to 480 nm, while a new band appears in the range 500 to 750 nm (strong change of color from colorless to green). The appearance of a new band in the visible region can be attributed to the formation of the phenazine radical cation (2a) and its 7π-electron delocalized pyrazine core.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…Pyrazine compounds are electron-deficient species. Hence, they are used in the design of n-type organic semiconductors examples are pyrazino quinoxaline derivatives, hexaazatriphenylenes, diquinoxalino, phenazine, and quinoxalinophenanthro phenazine [30]. Richards et al have shown that the pyrazinacene are good candidates as materials Richards for organicetal thin film transistors as shown in the Figure 1 [31].…”
Section: Current Trends In Fashion Technology and Textile Engineeringmentioning
confidence: 99%